ANALISIS SEKTOR UNGGULAN DALAM PENGEMBANGAN WILAYAH KABUPATEN KEPULAUAN MERANTI - Muhammad Hidayat; Ranti Darwin (MediaTrend, 2017)
Meranti Islands Regency is one of the areas that are expected to be the gate of trade in western Indonesia. The strategic position lies between the two corridors of the Masterplan for Acceleration and Expansion of Indonesian Economic Development (MP3EI), namely the Pekanbaru corridor and the Batam corridor. Seeing these opportunities are expected to accelerate regional development. This study aims to identify and analyze potential sectors of the economy and formulate future development policies. The analytical tools used are Location Quotient (LQ), Shift Share Analysis (SSA), and Specialization Index. This study used time series data in the period of 2010-2015. The analysis results indicate that potential sectors based on the combined analysis of Location Quationt, Shift Share Analysis, and Specialization Index are Transportation and Warehousing Sector; Agricultural, Forestry and Fishery Sectors; and Processing Industry Sector. The sectors that are specialized in inter-regional interactions are Agriculture, Forestry and Fishery Sectors; And Transportation and Warehousing Sector.